The economics of reindeer herding, Saami entrepreneurship between cyclical sustainability and the powers of state and oligopolies - Reinert , Erik S. (2006)
This paper attempts to explain the drastic fall in income experienced by Saami reindeer herders in Northern Norway between 1976 and 2000, in spite of increasing government subsidies.